THE EFFECT OF CORPORATE GOVERNANCE AND INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE WITH EARNINGS MANAGEMENT AS MEDIATION VARIABLE - Mariani, Mariani; Syaifuddin, Dedy Takdir; Sujono, Sujono; Usman, Usman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study examines the effect of corporate governance and intellectual capital on financial performance, with earnings management as a mediating variable, in banking companies listed on the Indonesia Stock Exchange during the 2017–2024 period. Using purposive sampling, 20 banks with a total of 160 observations were selected as the research sample. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that corporate governance and intellectual capital have a positive and significant effect on financial performance, with intellectual capital emerging as the most dominant factor. However, corporate governance and intellectual capital do not have a significant effect on earnings management. Furthermore, earnings management does not mediate the relationship between corporate governance or intellectual capital and financial performance. These findings suggest that improvements in financial performance within the banking sector are driven more by the direct implementation of sound corporate governance practices and effective management of intellectual capital rather than through earnings management practices.